2015
DOI: 10.4103/0973-8398.154688
|View full text |Cite
|
Sign up to set email alerts
|

Influence of excipients on drug absorption via modulation of intestinal transporters activity

Abstract: O ne of the major factors affecting oral drug bioavailability is the activity of intestinal transport proteins, particularly for the drugs that undergo absorption by active transport mechanism. Many of the active pharmacological agents and the excipients used in their formulation are reported to modulate the activity of these transporters thereby either enhancing or decreasing the drug absorption and its systemic availability. These excipients are considered pharmacologically "inert" and have been used since y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…Higher oil content was required for any higher drug loading capacity and also produced a lower proportion of the surfactant phase. However, a high proportion of the surfactant phase allowed for good characteristics of the formulations and also improved drug absorption . Therefore, the SMEDDS containing 45% of the C90 oil and surfactant phase (45% CRH40 and 10% Tw80) were formulated to compare with the lipid nanoparticle systems (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Higher oil content was required for any higher drug loading capacity and also produced a lower proportion of the surfactant phase. However, a high proportion of the surfactant phase allowed for good characteristics of the formulations and also improved drug absorption . Therefore, the SMEDDS containing 45% of the C90 oil and surfactant phase (45% CRH40 and 10% Tw80) were formulated to compare with the lipid nanoparticle systems (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the % surfactant phase (55% w/w) of the SMEDDS was about ten times greater than for the lipid nanoparticles system (5.625% w/w). Considering that Tw80 can be toxic, the specific mixture of Tw80 and other surfactant types might cause the difference . In addition, the greater % of Tw80 in the SMEDDS (10% w/w) than in the nanoparticles systems (3.75% w/w) indicated that the more toxic nature of the former system was most likely due to the concentration of the cytotoxic properties of the surfactants .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, some excipients in the formulation are also reported to alter the activity of intestinal transport proteins and thus can influence the absorption of the drug molecules. Therefore, the pharmaceutical excipients can alter the bioavailability and, in turn, the pharmacological effect of the drugs [29].…”
Section: Based Onmentioning
confidence: 99%